Cross-border B2C e-commerce to China: An evaluation of different logistics solutions under uncertainty. Issue 3 (13th December 2019) - Giuffrida, Maria; Mangiaracina, Riccardo; Perego, Alessandro; Tumino, Angela
Abstract : Purpose: The purpose of this paper is to support companies' risk-informed selection of a logistics solution to operate in China via cross-border e-commerce (CBEC). Design/methodology/approach: Decision theory is applied to the recent field of CBEC. This theoretic setup involves a decision maker who must choose among a set of alternatives, whose consequences depend on uncertain factors (Savage, 1954 ). The study develops an activity-based model to calculate logistics costs in a deterministic setting. Simulations and probabilistic sensitivity analyses are later performed to evaluate the impact of uncertainty. Findings: There are four main solutions to enter China, determined by the adopted international transport mean and the presence of a local warehouse. The most important risk factors affecting the choice of the logistics solution are change of CBEC regulation, product value, expected service level and demand level. Originality/value: From a theoretical perspective, this study improves CBEC literature, so far characterised by descriptive papers, often lacking industry focus or empirical exploration. It also provides new application opportunities for decision theory, whereas previous contributions have proposed different theoretical approaches, such as transaction cost or institutional theory. From a practical viewpoint, the paper is the first to compare the costs of the main logistics solutions to sell online to China, by taking uncertainty into account. The results can be used to better understand the differences among solutions and identify the most critical parameters. Finally, this research provides some observations for policy implementation.